الحق في الترشح للانتخابات في الجزائر - أكرم صلاح الدين محامدية; حسام نصايبية (My University, 2022)
Summary : It goes without saying that the right to candidacy is one of the political rights in which the individual expresses his will in an official capacity to occupy a certain position. The legislator granted him a set of principles and formal and other objective conditions to ensure that the right person reaches a certain political position. Therefore, after all conditions are met, exercising the right to run for candidacy requires mechanisms to ensure the integrity of the electoral process as it is a prominent stage, especially by organizing the electoral campaign in terms of its means and financing, not to mention the creation of electoral legislation for the Independent National Election Authority as a mechanism that works to protect the right to run, not to mention the The role of the Constitutional Court in monitoring appeals against nominations for the post of President of the Republic. ......................... الملخص : غني عن البيان أن حق الترشح من الحقوق السياسية التي يعبر فيها الفرد عن أرادته بصفة رسمية لتقلد منصب معين ، منح له المشرع مجموعة من المبادئ و شروط شكلية و أخرى موضوعية للحرص على وصول الشخص المناسب لتقلد منصب سياسي ما وعليه بعد توفر جميع الشروط ممارسة حق الترشح فإنه يحتاج إلى آليات تضمن نزاهة العملية الإنتخابية بإعتبارها المرحلة البارزة ، سيما من خلال تنظيم الحملة الإنتخابية من حيث وسائلها و تمويلها ، ناهيك عن إستحداث التشريع الإنتخابي للسلطة الوطنية المستقلة للإنتخابات كآلية تعمل على حماية حق الترشح ، ناهيك عن دور المحكمة الدستورية في الرقابة على الطعون في الترشيحات لمنصب رئيس الجمهورية